ROLE OF COMORBIDITIES IN OPTIMIZING DECISION-MAKING FOR ALLOGENEIC HEMATOPOIETIC CELL TRANSPLANTATION - Mohamed L. Sorror; Rainer F. Storb (Mediterranean Journal of Hematology and Infectious Diseases)
Allogeneic conventional hematopoietic cell transplantation (HCT) following high-dose, myeloablative conditioning regimens has been used since the 1970’s as potentially curative treatment for patients with malignant, hematological disorders. The toxicities of conditioning regimens have limited conventional HCT to relatively young patients in otherwise good medical condition. With the development of less toxic nonmyeloablative regimens and improvements in supportive care, increasing numbers of older and medically infirm patients have been treated by allogeneic HCT. Until recently, there has been almost no effort to evaluate the prevalence of comorbidities among HCT recipients and their impact on outcomes. We first evaluated the Charlson Comorbidity Index (CCI) developed for patients with solid malignancies, for this purpose. While useful, it lacked sensitivity and specificity for the HCT setting. We next introduced the HCT-specific comorbidity index (HCT-CI) which was based on objective laboratory data to better define comorbidities. Here, we describe this development and illustrate the usefulness of the HCT-CI in predicting HCT outcomes in patients with myeloid and lymphoid malignancies undergoing allogeneic transplantation